IoT-based temperature, humidity, and ammonia control system for chicken coop - Budiman, Arif; Muskhir, mukhlidi (Department of Electrical Engineering Universitas Negeri Padang, 2025)
This research has designed and developed an integrated IoT (Internet of Things)-based system for controlling temperature, humidity, and ammonia levels in chicken coops. The study involved several experiments to test the functionality and effectiveness of the built system. Based on the results obtained from the assembly process, programming, device construction, and comprehensive system testing, it can be concluded that this control system application is effective in improving farmers' work efficiency. The automated waste removal is capable of lowering ammonia levels, minimizing manual labor, and efficiently saving time. Furthermore, this device functions to monitor and maintain the temperature for the livestock inside the coop. The device, with inputs and outputs from DHT-22 and MQ-135 sensors, an ESP32 microcontroller, a heating element, a conveyor, and a DC motor, has been successfully operated and proven effective in regulating temperature and ammonia gas levels in chicken coops.